Distribute on the left side
7.4a+22.2=3.2a+43.2
Subtract 3.2a from both sides
4.2a+22.2=43.2
Subtract 22.2 from both sides
4.2a=21
Divide both sides by 4.2
a=5
Answer:
<em>Correct answer:</em>
<em>A. I and II</em>
<em></em>
Step-by-step explanation:
First of all, let us have a look at the steps of finding inverse of a function.
1. Replace y with x and x with y.
2. Solve for y.
3. Replace y with ![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
Given that:
![I.\ y=x \\II.\ y=\dfrac{1}x \\III.\ y=x^2 \\IV.\ y=x^3](https://tex.z-dn.net/?f=I.%5C%20y%3Dx%20%5C%5CII.%5C%20y%3D%5Cdfrac%7B1%7Dx%20%5C%5CIII.%5C%20y%3Dx%5E2%20%5C%5CIV.%5C%20y%3Dx%5E3)
Now, let us find inverse of each option one by one.
I. y = x, a(x) = x
Replacing y with and x with y:
x = y
x =
=
Hence, I is true.
II. ![y =\dfrac{1}{x}](https://tex.z-dn.net/?f=y%20%3D%5Cdfrac%7B1%7D%7Bx%7D)
Replacing y with and x with y:
![x =\dfrac{1}{y}](https://tex.z-dn.net/?f=x%20%3D%5Cdfrac%7B1%7D%7By%7D)
=
Hence, II is true.
III. ![y =x^{2}](https://tex.z-dn.net/?f=y%20%3Dx%5E%7B2%7D)
Replacing y with and x with y:
Hence, III is not true.
IV. ![y =x^{3}](https://tex.z-dn.net/?f=y%20%3Dx%5E%7B3%7D)
Replacing y with and x with y:
Hence, IV is not true.
<em>Correct answer:</em>
<em>A. I and II</em>
<em></em>
You used to say "y = 2x + 3; solve<span> for y when x = –1". Now you say "f(x) = 2x + 3; find f(–1)" (pronounced as "f-of-x is 2x plus three; find f-of-negative-one"). You do exactly the same thing in either case: you plug in –1 for x, multiply by 2, and then add the 3, simplifying to get a final value of +1.
Brainliest?</span>